2010
DOI: 10.1007/s10637-010-9408-4
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of sorafenib in first-line metastatic urothelial cancer: a study of the PMH Phase II Consortium

Abstract: Sorafenib does not show sufficient activity as a single agent in first-line metastatic urothelial cancer to warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 23 publications
1
38
0
1
Order By: Relevance
“…Sorafenib is a TKI that blocks cellular proliferation via the ERK pathway and angiogenesis via the VEGF pathway. A first-line trial in chemona€ ve patients showed no ORs, a TTP of 1.9 months, and MS of only 5.9 months, consistent with second-line findings (55,56). A study of GC plus sorafenib showed significant toxicity (57).…”
Section: Anti-vegf Therapysupporting
confidence: 57%
“…Sorafenib is a TKI that blocks cellular proliferation via the ERK pathway and angiogenesis via the VEGF pathway. A first-line trial in chemona€ ve patients showed no ORs, a TTP of 1.9 months, and MS of only 5.9 months, consistent with second-line findings (55,56). A study of GC plus sorafenib showed significant toxicity (57).…”
Section: Anti-vegf Therapysupporting
confidence: 57%
“…Although some positive preclinical studies have been reported, no satisfactory results in terms of clinical benefit have been obtained by the use of VEGFR-TKIs in bladder cancer [78][79][80][81][82][83]. A better knowledge of the mechanisms of VEGFR-TKI-induced cell death may represent a major step forward in identifying potential target for drug resistance.…”
Section: Resistance To Vegf/vegfr Inhibitorsmentioning
confidence: 99%
“…Thus, several trials with sunitinib, sorafenib and pazopanib have been performed (21)(22)(23)(24). Sunitinib is preclinically active against urothelial carcinoma (25).…”
Section: Commentsmentioning
confidence: 99%